If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + 2(6x + -8) = 2x + -1(5 + -2x + 51) Reorder the terms: 30 + 2(-8 + 6x) = 2x + -1(5 + -2x + 51) 30 + (-8 * 2 + 6x * 2) = 2x + -1(5 + -2x + 51) 30 + (-16 + 12x) = 2x + -1(5 + -2x + 51) Combine like terms: 30 + -16 = 14 14 + 12x = 2x + -1(5 + -2x + 51) Reorder the terms: 14 + 12x = 2x + -1(5 + 51 + -2x) Combine like terms: 5 + 51 = 56 14 + 12x = 2x + -1(56 + -2x) 14 + 12x = 2x + (56 * -1 + -2x * -1) 14 + 12x = 2x + (-56 + 2x) Reorder the terms: 14 + 12x = -56 + 2x + 2x Combine like terms: 2x + 2x = 4x 14 + 12x = -56 + 4x Solving 14 + 12x = -56 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 14 + 12x + -4x = -56 + 4x + -4x Combine like terms: 12x + -4x = 8x 14 + 8x = -56 + 4x + -4x Combine like terms: 4x + -4x = 0 14 + 8x = -56 + 0 14 + 8x = -56 Add '-14' to each side of the equation. 14 + -14 + 8x = -56 + -14 Combine like terms: 14 + -14 = 0 0 + 8x = -56 + -14 8x = -56 + -14 Combine like terms: -56 + -14 = -70 8x = -70 Divide each side by '8'. x = -8.75 Simplifying x = -8.75
| 2x^3-5x^2-10x+1=0 | | -(6x+6)+16x=33 | | x^3-5x^2-10x+5=0 | | 21=5t^2+25t | | 1/7*Ln(x) | | 14d+9=5d+45 | | 3x/5=13 | | 9n^4-10n^2+1=0 | | 5(x-5)=-11.5 | | 3(a+5)=35.1 | | 8.3=3c-1 | | 9e-2=28.6 | | 2p=6.8 | | Y=30x+216 | | (X*X)+15=11 | | 53=6x-1 | | 0=-4+x+0.75x^2 | | X*2+15=11 | | 5m-10-4m-7=0 | | k-8/3=19/3 | | 1600-2Q= | | 3sin(2x+10)=2 | | -2.4+j=-1.8 | | 1700-2Q= | | -10(s+4)=-106 | | Z^4=6z^2+7 | | 5(y+-4)=35 | | 5y+4=35 | | 27=3(2x-3) | | 4-5x+20-6x=68 | | 8x+28=4(x+5) | | -36=8x-11x |